UJI AKTIVITAS ANTIBAKTERI DARI EKSTRAK METANOL DAUN DOLAR (FICUS PUMILA L.) TERHADAP BAKTERI Streptococcus mutans DAN Salmonella typhi DENGAN MENGGUNAKAN METODE DIFUSI AGAR - Marulak Sehat Sinaga; Daniel Daniel; Saibun Sitorus; Agustina Rahayu M. (PROSIDING SEMINAR KIMIA, 2022)
Phytochemical screening and antibacterial activity from methanol extract of Dollar leaves (Ficus pumila L.) against Streptococcus mutans and Salmonella typhi bacteria has been done. The extraction was done by maceration extraction using methanol. Phytochemical test showed Ficus pumila L. contains secondary metabolites including alkaloids and steroids. Antibacterial activity test using diffusion methode of agar by well and disc indicate the presence of antibacterial activity (same MIC among concentration 0-0.625%) againts Streptococcus mutans and Salmonella typhi bacteria. The diameter range againts Streptococcus mutans and Salmonella typhi bacteria by well including with 13.5 mm (strong antibacterial activities) dan 16.67 mm (strong antibacterial activities) while by paper disc including with 15.66 mm (strong antibacterial activities) dan 16.3 mm (strong antibacterial activities). Keywords: Phytochemical, Antibactery, Dollar Leaves (Ficus pumila L.), Agar Diffusion